3D Interpretation of a Broadband Magnetotelluric Data Set Collected in the South of the Chinese Zhongshan Station at Prydz Bay, East Antarctica - Enzhao Xiao; Feng Jiang; Jingxue Guo; Khalid Latif; Lei Fu; Bo Sun (Remote Sensing, 2022)
Antarctica is covered by a thick ice sheet, and the application of geophysical methods is necessary to image the subglacial structures for studying the hydrologic systems and tectonic deformations in the Antarctic continent. The magnetotelluric (MT) method is one of the best approaches to obtain the subglacial electrical resistivities. However, only a very small volume of data has been collected so far in Antarctica using this method. In this paper, we report on a broadband MT profile collected at 10 sites in the south of the Chinese Zhongshan Station at Prydz Bay, and a 3D resistivity model was constructed by inversion of these data. This 3D model shows two low resistivity zones at a depth shallower than 6 km. They are consistent with the low-velocity zones in the previous shear-wave model and can be interpreted as the result of interconnected fluids associated with a downward migration of subglacial water. In addition, a distinct eastward dipping low resistivity zoneis present in the crust, which extends from the top surface to the lower crust. Since its location coincides with the highly positive magnetization named Amery Lineament, it is proposed that this eastward dipping low resistivity zoneextending in the entire crust probably reveals the geometry structure of the Amery Lineament at depth. Besides, it can be inferred from this new 3D resistivity model that the Amery Lineament is at least a crustal-scale structure, which probably outcrops on the land surface but was covered by the ice sheets in the study area.